Hydroponic smart farming using cyber physical social system with telegram messenger - Sisyanto, Robert Eko Noegroho; Suhardi; Kurniawan, Novianto Budi (ICITSI : proceedings : 2017 International Conference on Information Technology Systems and Innovation : October 23-24, 2017, Bandung, Indonesia, 2017)
In the Cyber Physical Social System (CPSS), collaborative work between hydroponic farmers is now possible. With this new concept, hydroponic smart farming system that can be monitored online via Telegram Messenger is developed. The design that is created can monitor important parameters in the hydroponics system, such as light intensity, room temperature, humidity, pH, nutrient temperature, and Electrical Conductivity (EC). The prototype is designed using Raspberry Pi 3 that connects directly with sensors such as DHT11 module, LDR, pH sensor module, and EC sensor. Telegram BOT that allows to monitor sensors online via Telegram is also made. With the integration of the Physical System (Raspberry Pi, sensor) and Social System (Telegram Messenger) connected online via internet or cyber, the hydroponic system monitoring becomes more flexible.